Four ppm measurement of the antihydrogen ground-state hyperfine splitting - R. Akbari; L. O. de Araujo Azevedo; C. J. Baker; W. Bertsche; N. M. Bhatt; G. Bonomi; A. Capra; I. Carli; M. Charlton; A. Cridland Mathad; D. Duque Quiceno; S. Eriksson; et al. (Nature, 2026)
Abstract The hydrogen atom is a touchstone for the foundations, evolution and frontiers of quantum theory 1–9 . Key spectral lines of this atom have been determined to remarkable precision 10,11 . Our research focuses on the study of antihydrogen, the antimatter counterpart of hydrogen. We test fundamental symmetries of nature (such as simultaneous charge conjugation, parity inversion, and time reversal or CPT symmetry) through precision comparisons of these atomic systems 12 . Recent 1S–2S spectroscopic measurements on trapped antihydrogen have achieved relative precisions of parts per trillion (refs. 13,14 ). However, the ground-state hyperfine splitting, which is sensitive to the internal structure of the antiproton, has only been measured to 400 parts per million (ppm). Here we report a 4 ppm measurement of the antihydrogen ground-state hyperfine splitting energy a 1S , advancing the state-of-the-art precision 15 by two orders of magnitude. From microwave spectroscopy experiments with roughly 24,000 anti-atoms, we determine $${a}_{1{\rm{S}}}/h=1,420,404.8± 1.1(stat.)± 5.6\,(sys.)\,\text{kHz}$$ a 1 S / h = 1,420,404.8 ± 1.1 ( stat. ) ± 5.6 ( sys. ) kHz in a 1-T magnetic field, consistent with expectations for hydrogen 11 . At this level, our measurement is sensitive to the internal structure of the antiproton, which contributes at about 40 ppm and is approaching the limit of existing theoretical analyses 16 . The gains we report are the product of marked advances in magnetic trap field control, stabilization and characterization; anti-atom spin-state manipulation; and improved antihydrogen accumulation rate 17 .